SEG Technical Program Expanded Abstracts 2015 2015
DOI: 10.1190/segam2015-5852423.1
|View full text |Cite
|
Sign up to set email alerts
|

An integrated, multi-disciplinary approach utilizing stratigraphy, petrophysics, and geophysics to predict reservoir properties of tight unconventional sandstones in the Powder River Basin, Wyoming, USA

Abstract: Numerous unconventional resources have become economically viable with the development of horizontal drilling and multi-stage hydraulic fracturing. Unconventional reservoirs have variable degrees of heterogeneity and identification of good and poor reservoir properties is essential for efficient development to define the economic limits of a resource play. An integrated, multidisciplinary approach of correlating core facies to petrophysical wireline facies to seismic facies for tight unconventional sandstones … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 3 publications
0
1
0
Order By: Relevance
“…Therefore, the productivity of a horizontal well is affected by characteristics of the well including the wellbore length, hydraulic fracture conductivities, and number of fracture stages as well as reservoir properties such as including porosity, permeability, rock compressibility, and natural fractures, etc. (Zawila et al, 2015). Many of the low-permeability unconventional formations where multi-stage hydraulic fracturing operations are generally utilized exhibit heterogeneity in reservoir properties.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the productivity of a horizontal well is affected by characteristics of the well including the wellbore length, hydraulic fracture conductivities, and number of fracture stages as well as reservoir properties such as including porosity, permeability, rock compressibility, and natural fractures, etc. (Zawila et al, 2015). Many of the low-permeability unconventional formations where multi-stage hydraulic fracturing operations are generally utilized exhibit heterogeneity in reservoir properties.…”
Section: Introductionmentioning
confidence: 99%
“…The other assumption is that the formation properties around each fracture are assumed to be the same, and the interference between different fractures is not investigated. However, Zawilla [13] and Liu [14] indicated that heterogeneous properties are commonly existed in the unconventional reservoir formation and different fracturing stages.…”
Section: Introductionmentioning
confidence: 99%